Global Value Chains : What are the Benefits and Why Do Countries Participate? - Raei, Faezeh (IMF Working Papers; Working Paper ;, 2019)
Over the last two decades, world trade and production have become increasingly organized around global value chains (GVC). Recent theoretical work has shown that countries can benefit from participation in GVCs through multiple channels. However, little is known empirically about the economic importance of supply chains. We use the Eora MRIO database to compute different measures of GVC participation for 189 countries and illustrate global patterns of supply chains as well as their evolution over time in order to contribute to this topic. We find that GVC-related trade, rather than conventional trade, has a positive impact on income per capita and productivity, however there is large heterogeneity and the gains appear more signifcant for upper-middle and high-income countries. We document that 'moving up' to more high-tech sectors while participating in major supply chains does take place but is not universal, suggesting other factors matter. We confirm the findings of the standard gravity literature for GVC trade; highlighting the key role of institutional features such as contract enforcement and the quality of infrastructure as determinants of GVC participation.